Asymbiotic Culture of Immature Embryos, Mass Multiplication of Cymbidium Iridioides D. Don. and the Role of Different Factors - Aolemla Pongener; Chitta Ranjan Deb (International Journal of Pharma and Bio Sciences, 2010)
Immature embryos of Cymbidium iridioides were successfully cultured on five different media with various supplements and maintained in three different light conditions. Within three week of culture, embryos formed nodular structures. Cultures under full light condition formed green protocorm-like bodies while, other light conditions failed to support optimum germination. Immature embryos of 10 months after pollination registered optimum germination ( 95%) on MS medium containing sucrose (2%), CW (5%) and NAA + BA (3 +3 µM in combination). The germinated embryos formed PLBs and differentiated within two passages on germination media. The advanced protocorm-like bodies were converted into rooted plantlets on MS medium containing sucrose (3%), NAA (3 µM) and BA (6 µM) where as many as 20 shoot buds/PLBs developed. The rooted plantlets were hardened on ½MS medium with sucrose (1%) and charcoal, brick pieces and chopped mosses (at 1:1 ratio) as substratum for 4-6 wk before transferring to community potting mix. About 80% survival rate was registered after two months of potting.